2008
DOI: 10.1016/j.jtcvs.2007.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of hematocrit 25% versus 35% during hypothermic cardiopulmonary bypass in infant heart surgery

Abstract: Hemodilution to hematocrit levels of 35% compared with those of 25% had no major benefits or risks overall among infants undergoing 2-ventricle repair. Developmental outcomes at age 1 year in both randomized groups were below those in the normative population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 20 publications
4
92
2
1
Order By: Relevance
“…This observation was previously reported in preterm infants by our group [38]. These findings support the importance of maintaining HGB levels in the perioperative period [70]. In addition, these data underscore the need for not only further research, but also new devices, to fully investigate neurodevelopmental outcomes and cerebral physiology in CHD patients.…”
Section: Discussionsupporting
confidence: 89%
“…This observation was previously reported in preterm infants by our group [38]. These findings support the importance of maintaining HGB levels in the perioperative period [70]. In addition, these data underscore the need for not only further research, but also new devices, to fully investigate neurodevelopmental outcomes and cerebral physiology in CHD patients.…”
Section: Discussionsupporting
confidence: 89%
“…All invited investigators agreed to submit data for this analysis. 8,9,[15][16][17][18][19][20][21][22][23][24] …”
Section: Identification Of Participating Institutionsmentioning
confidence: 99%
“…The first study showed in 113 children younger than 9 months that hemodilution during CPB to hematocrit of 21.5 % (Hb & 7.5 g/dL) compared to 27.8 % (Hb & 9.3 g/dL) was associated with lower Bayley Psychomotor Development index at 1 year of age (81.9 ± 15.7 vs. 89.7 ± 14.7, p = 0.008) [20]. However, in a different study of 124 patients, the same psychomotor development index was similar at 1 year of age in subjects with hematocrits of 24.8 % (Hb & 8.3 g/dL) and 32.6 % (Hb & 10.9 g/dL) during CPB [21]. A subgroup analysis of 125 infants enrolled in the TRIPICU study after cardiac surgery [12] showed no significant difference in incidence of multiple organ dysfunction syndrome and death (12.7 vs. 6.3 %; p = 0.36) when comparing restrictive and liberal transfusion groups (Hb: 7.0 vs. 9.5 g/dL); however, neonates and patients with cyanotic heart disease were excluded from this trial [14].…”
Section: Discussionmentioning
confidence: 88%